1994
DOI: 10.1021/ac00094a037
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Separation from S-Block and Other Elements Using a Polymeric Crown Ether

Abstract: A very simple column chromatographic separation method has been developed for potassium. The separation of potassium was carried out using poly(dibenz0-18-crown-6) with hydrobromic acid medium. Large amounts of sodium and rubidium were separated from trace level potassium. Potassium was separated from a number of associated elements in tertiary and four-component systems. The proposed method was extended to the analysis of potassium in various rocks and biological and medicinal samples. The method is very simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…230243 for (1) and 230244 for (2). Copies of this information may be obtained free of charge from the Director, CCDC, 12 Union Road, Cambridge, CB2,1EZ, UK (fax: +44-1223-336033; email: deposit@ccdc.cam.uk or http://www.ccdc.cam.ac.…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…230243 for (1) and 230244 for (2). Copies of this information may be obtained free of charge from the Director, CCDC, 12 Union Road, Cambridge, CB2,1EZ, UK (fax: +44-1223-336033; email: deposit@ccdc.cam.uk or http://www.ccdc.cam.ac.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The first-row transition metal(II) complexes with polyaza macrocyclic ligands have attracted considerable interest due to their importance as metal ion-selective reagents [1][2][3] and models for metalloenzyme active sites [4][5][6]. It has been widely observed that the structures and chemical properties of metal complexes with these ligands are influenced by several factors, including the metal ion size, anionic groups and ligand topology, such as the cavity size, type and number of donor atoms, and stereochemical rigidity [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Syntheses of macrocycles were sometimes limited due to side reactions and polymerization, but metal template synthesis offers an alternative high yielding and often selective route to macrocyclic ligands with a range of geometries and potential uses [1,2]. Macrocyclic complexes of transition metal ions have a number of unique properties offered by the macrocyclic environment, such as extremely high thermodynamic stability, the ability to access unusual oxidation states of the metal [3], metal ion-selective reagents [4][5][6], models for metalloenzyme active sites [7,8], applications in biology and medicine and also as catalysts for conversion of various organic substrates [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The application of polyaza macrocycle precursors in the synthesis of transition metal(II) macrocyclic complexes stems mainly from their use as models for protein-metal binding sites in biological systems [1][2][3][4], and as selective complexing agents for metal ions [5][6][7][8]. Recently, the cyclam and modified cyclam cobalt(III) complexes have been synthesized and structurally characterized by spectroscopy and X-ray crystallography [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%